1994
DOI: 10.1037/0278-7393.20.5.1063
|View full text |Cite
|
Sign up to set email alerts
|

Remembering can cause forgetting: Retrieval dynamics in long-term memory.

Abstract: Three studies show that the retrieval process itself causes long-lasting forgetting. Ss studied 8 categories (e.g., Fruit). Half the members of half the categories were then repeatedly practiced through retrieval tests (e.g., Fruit Or). Category-cued recall of unpracticed members of practiced categories was impaired on a delayed test. Experiments 2 and 3 identified 2 significant features of this retrieval-induced forgetting: The impairment remains when output interference is controlled, suggesting a retrieval-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

134
1,972
23
20

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,121 publications
(2,184 citation statements)
references
References 67 publications
(125 reference statements)
134
1,972
23
20
Order By: Relevance
“…Typically, studies that have explored retrieval-induced forgetting effects have reported differences between RpϪ and Nrp recall performance in the region of Ϫ.10 to Ϫ.19 (see M. C. Anderson et al, 1994; M. C. Anderson & Spellman, 1995;MacLeod, 2002;MacLeod & Macrae, 2001;Macrae & MacLeod, 1999). If our contention is correct, we can make a number of specific predictions.…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…Typically, studies that have explored retrieval-induced forgetting effects have reported differences between RpϪ and Nrp recall performance in the region of Ϫ.10 to Ϫ.19 (see M. C. Anderson et al, 1994; M. C. Anderson & Spellman, 1995;MacLeod, 2002;MacLeod & Macrae, 2001;Macrae & MacLeod, 1999). If our contention is correct, we can make a number of specific predictions.…”
mentioning
confidence: 72%
“…We argue that one of the potential mechanisms underlying misinformation effects is retrieval-induced forgetting (i.e., the forgetting of information as a function of remembering other related material; see M. C. Anderson, Bjork, & Bjork, 1994; M. C. Anderson & Spellman, 1995). This effect is thought to be due to the active suppression or inhibition of unwanted material at time of retrieval.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Incomplete narratives also tend to be less well organized , and retelling of them affords less rehearsal benefit . Incomplete narrative rehearsal may even result in retrieval-induced forgetting, the phenomenon by which retrieving some elements of a memory trace may result in forgetting of nonretrieved elements (e.g., Anderson, Bjork, & Bjork, 1994), with resultant further trace degradation. Thus, developments in verbal and narrative skill herald cognitive benefits of rehearsal and organization, which are advantageous to memory.…”
mentioning
confidence: 99%